Comparative Analysis of Genomic and Transcriptome Sequences Reveals Divergent Patterns of Codon Bias in Wheat and Its Ancestor Species - Yang, Chenkang; Zhao, Qi; Wang, Ying; Zhao, Jiajia; Qiao, Ling; Wu, Bangbang; Yan, Suxian; Zheng, Jun; Zheng, Xingwei (Frontiers in Genetics, 2021)
The pattern of synonymous codons usage shows a characteristic pattern of preference in each organism. This codon usage bias is thought to have evolved for efficient protein synthesis. Synonymous codon usage was studied in genes of the hexaploid wheat T. aestivum (AABBDD) and its progenitor species, Triticum urartu (AA), Aegilops tauschii (DD), and Triticum turgidum (AABB). T. aestivum exhibited stronger usage bias for G/C-ending codons than did the three progenitor species and this bias was especially higher compared to T. turgidum and Ae. Tauschii. High GC content is a primary factor influencing codon usage in T. aestivum. Neutrality analysis showed a significant positive correlation (p < 0.001) between GC12 and GC3 in the four species with regression line slopes near zero (0.16~0.20), suggesting that the effect of mutation on codon usage was only 16%~20%. The GC3s values of genes were associated with gene length and distribution density within chromosomes. tRNA abundance data indicated that codon preference corresponded to the relative abundance of isoaccepting tRNAs in the four species. Both mutation and selection have affected synonymous codon usage in hexaploid wheat and its progenitor species. GO enrichment showed that GC biased genes were commonly enriched in physiological processes such as photosynthesis and response to acid chemical. In some certain gene families with important functions, the codon usage of small parts of genes have changed during the evolution process of T. aestivum.